Art Forgery : the History of a Modern Obsession. - Lenain, Thierry (Reaktion Books, 2012)
With the recent advent of technologies that make detecting art forgeries easier, the art world has become increasingly obsessed with verifying and ensuring artistic authenticity. In this unique history, Thierry Lenain examines the genealogy of faking and interrogates the anxious, often neurotic, reactions triggered in the modern art world by these clever frauds. Lenain begins his history in the Middle Ages, when the issue of false relics and miracles often arose. But during this time, if a relic gave rise to a cult, it would be considered as genuine even if.